The Association of Abnormal Doppler and Abnormal Amniotic Fluid Volume in the Third Trimester of Pregnancy with Preterm Birth in Pregnant Women in Agra, India - Gupta, Anjali; Choorakuttil, Rijo Mathew; Nirmalan, Praveen K. (Indian Journal of Radiology and Imaging, 2023)
Aim This article determines the association and diagnostic effectiveness of abnormal Doppler and abnormal amniotic fluid volume (AFV) in the third trimester of pregnancy with preterm births.Methods The third trimester screening protocol of the Samrakshan program of the Indian Radiological and Imaging Association utilizes trimester-specific fetal Doppler studies and ultrasound assessments, estimation of the risk for preterm preeclampsia (PE), assessment of the fetal environment, growth, and structure, and staging of fetal growth restriction. A multivariate logistic regression model was used to explore associations of abnormal Doppler and AFV with preterm birth. The diagnostic effectiveness of Doppler and amniotic fluid measurements for preterm births was assessed.Results One hundred and sixty-one (25.6%) of the 630 women had a preterm birth before 37 gestational weeks. Eighty (21.1%) of the 379 women with normal AFV and normal fetal Doppler studies in the third trimester had a preterm birth. The proportion of preterm birth declined from 35.14% in 2019 to 19.53% in 2022 (chi-square test p = 0.009). Preterm birth was associated with preterm PE (adjusted odds ratio: 3.66, 95% confidence interval: 1.42, 9.44) in a multivariate logistic regression model. Both abnormal fetal Doppler and AFV did not have a good discriminatory ability for preterm births.Conclusion Integration of fetal Doppler studies helped reduce the preterm birth rate by providing an objective measure of fetal well-being, contrary to a common belief that the use of color Doppler in the third trimester may result in iatrogenic increased preterm birth. Preterm births are associated with preterm PE and early identification of high-risk women and early initiation of low-dose aspirin may have an added benefit on preterm birth rates.
Keywords: amniotic fluid volume; fetal Doppler; preterm birth; preeclampsia; pregnancy